Association of antioxidant status and inflammatory markers with metabolic syndrome in Thais - Kanjana Suriyaprom; Sarunya Kaewprasert; Pumpath Putpadungwipon; Pisit Namjuntra; Suwit Klongthalay (BMC, 2019)
Abstract Background An oxidant/antioxidant disequilibrium has been suggested as having a role in the pathogenesis of some diseases. Metabolic syndrome (MS) is significantly associated with cardiovascular disease and type 2 diabetes. The pathogenesis of MS is complex and not well understood. The purposes of the present study were to compare enzymatic and non-enzyme antioxidants, anthropometric, hematological, and biochemical findings between subjects with MS and without MS and to evaluate the relationship between antioxidant status and hematological parameters with the components of MS. Methods Metabolic syndrome was assessed by using the modified National Cholesterol Education Program, Adult Treatment Panel III criteria. Three hundred Thais, 124 with MS and 176 without MS, were included in the study. Each subject was tested for erythrocyte superoxide dismutase (SOD), glutathione peroxidase, (GPX), catalase (CAT), albumin and vitamin C levels, and hematological findings. Results Subjects with MS had lower SOD and CAT levels than those without MS (p < 0.01). Subjects with MS had lower vitamin C and albumin levels than those without MS (p < 0.05). The hematological findings were not significantly different between those with and without MS except the white blood cell (WBC) count which was significantly higher in those with MS. SOD and CAT levels were significantly positively associated with HDL-C levels and negatively associated with components of MS. After adjusting for potential covariates, we found lower SOD and vitamin C levels and higher WBC counts were significantly associated with MS (p < 0.05). Conclusions These findings suggest an alteration in antioxidant status and an increase in inflammatory markers are associated with MS and its components among Thais; subjects with MS may be more likely to have oxidative stress problems.